2022
DOI: 10.1515/ling-2020-0098
|View full text |Cite
|
Sign up to set email alerts
|

Caused motion events in Modern Uyghur: a typological perspective

Abstract: Talmy’s motion event typology (Talmy, Leonard. 2000. Towards a cognitive semantics: Conceptual structuring systems, vol. 2. Cambridge, MA: The MIT Press) has served as an influential framework for exploring event representation across languages. While confirming its basic premises, many studies argued that the typology cannot fully capture the vast intra- and inter-typological variations. Consequently, proposals have been made to expand the typology and/or reconceptualize it as a typology of constructional str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The other option was to choose motion events in which an agent displaces an object in a specific manner so that the object moves along a path, known as cause motion. We chose caused motion for this study to increase its relevance for, and connectivity, with a growing body of experimental work using this motion event type (Ji et al, 2011b; Ji & Hohenstein, 2014a, 2014b; Montero-Melis & Bylund, 2017; Tusun, 2023; Tusun & Hendriks, 2022; Wang & Wei, 2021). Another motivation was to partially replicate and enhance recent experimental work on the early stages of caused motion processing across Mandarin versus English speakers (Vanek & Fu, 2023), verifying the suitability of b-CFS as a method that can probe into the automatic processing of dynamic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The other option was to choose motion events in which an agent displaces an object in a specific manner so that the object moves along a path, known as cause motion. We chose caused motion for this study to increase its relevance for, and connectivity, with a growing body of experimental work using this motion event type (Ji et al, 2011b; Ji & Hohenstein, 2014a, 2014b; Montero-Melis & Bylund, 2017; Tusun, 2023; Tusun & Hendriks, 2022; Wang & Wei, 2021). Another motivation was to partially replicate and enhance recent experimental work on the early stages of caused motion processing across Mandarin versus English speakers (Vanek & Fu, 2023), verifying the suitability of b-CFS as a method that can probe into the automatic processing of dynamic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The seemingly superficial structural differences across languages outlined above have been found to have implications for habitual language use, particularly in terms of what aspects of motion events speakers typically profile and how often. Numerous crosslinguistic studies on motion expression have repeatedly demonstrated that S-language speakers show greater tendency to encode the framing event and the coevent simultaneously than their V-language counterparts, thereby rendering their motion descriptions semantically denser compared to those of the latter (e.g., Hendriks et al, 2021; Hickmann et al, 2009; Montero-Melis, 2021; Özçalışkan, 2015; Slobin, 2004; Tusun, 2022b; Tusun & Hendriks, 2019, 2022). The difference in semantic density has been attributed to different syntactic packaging constraints that S- versus V-languages impose on the speaker.…”
Section: Motion Event Typology and Language Usementioning
confidence: 99%
“…Interestingly, variability in syntactic packaging strategies in V-languages is not always observed. In a recent study, Tusun and Hendriks (2022) showed that speakers of Turkic languages are highly systematic in their syntactic packaging when expressing CM. They explained the lack of variability in Turkic in terms of word order effects.…”
Section: Motion Event Typology and Language Usementioning
confidence: 99%
See 2 more Smart Citations